2012 11th International Conference on Information Science, Signal Processing and Their Applications (ISSPA) 2012
DOI: 10.1109/isspa.2012.6310543
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of scoliosis trunk deformities using ICA

Abstract: This paper describes a method for analyzing scoliosis trunk deformities using Independent Component Analysis (ICA). Our hypothesis is that ICA can capture the scoliosis deformities visible on the trunk. Unlike Principal Component Analysis (PCA), ICA gives local shape variation and assumes that the data distribution is not normal. 3D torso images of 56 subjects including 28 patients with adolescent idiopathic scoliosis and 28 healthy subjects are analyzed using ICA. First, we remark that the independent compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, local 0000-0000/00$00.00 c 2011 IEEE trunk deformations such as asymmetry of the shoulders, waist or scapulae cannot been characterized by these functional indices. Thus, in our recent work [1], we have proposed a method for analyzing scoliotic trunk deformities using Independent Component Analysis (ICA), and have shown that the independent components capture the local scoliosis deformations.…”
Section: Introductionmentioning
confidence: 99%
“…However, local 0000-0000/00$00.00 c 2011 IEEE trunk deformations such as asymmetry of the shoulders, waist or scapulae cannot been characterized by these functional indices. Thus, in our recent work [1], we have proposed a method for analyzing scoliotic trunk deformities using Independent Component Analysis (ICA), and have shown that the independent components capture the local scoliosis deformations.…”
Section: Introductionmentioning
confidence: 99%